2019
DOI: 10.1111/his.13863
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33 overexpression in gallbladder cancers associated with pancreatobiliary maljunction

Abstract: Histopathology 75, 365-375. https://doi.org/10.1111/his.13863 IL-33 overexpression in gallbladder cancers associated with pancreatobiliary maljunctionAims: To investigate whether genetic or inflammatory pro-oncogenic factors are relevant to the increased risk of gallbladder cancers in patients with pancreaticobiliary maljunction (PBM). Methods and results: Mutations in KRAS exon 2 were examined by a highly sensitive, droplet digital PCR platform using surgically resected specimens of PBM-associated (n = 31) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Out of 92 articles, 30 were excluded due to: no data for adenocarcinoma of the gallbladder available (N = 12), overlapping cohorts (N = 8), the wrong type of article (N = 5), no genetic alteration frequency data available (N = 3), wrong study population (N = 1), and not written in English (N = 1). A total of 62 articles were included for final data extraction, describing a total of 3893 GBC samples from individual patients [ 18 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 92 articles, 30 were excluded due to: no data for adenocarcinoma of the gallbladder available (N = 12), overlapping cohorts (N = 8), the wrong type of article (N = 5), no genetic alteration frequency data available (N = 3), wrong study population (N = 1), and not written in English (N = 1). A total of 62 articles were included for final data extraction, describing a total of 3893 GBC samples from individual patients [ 18 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
“… China Li 2019 [ 18 ] 6/54 11% NGS AC Greece Papadopoulou 2018 [ 40 ] 8/21 38% PCR-RFLP AC India Singh 2004 [ 63 ] 8/34 24% Seq AC India Sharma 2017 [ 65 ] 9/81 11% PCR N.A. Japan Tomioka 2019 [ 45 ] 10/17 59% …”
Section: Table A1mentioning
confidence: 99%
“…In addition, some previous studies reported that KRAS mutations are more frequent in PBM-associated events than de novo gallbladder carcinomas [ 61 , 62 ]. In contrast, recent studies showed that the frequency of KRAS mutations is <20% in PBM-associated gallbladder cancer, which is comparable to that in non-PBM-associated gallbladder cancer [ 64 ]. According to our study data, KRAS mutations are not frequent events in gallbladder carcinogenesis in PBM [ 55 ].…”
Section: Pancreatobiliary Maljunctionmentioning
confidence: 99%
“…IL33 administration promoted the growth of Kras and TGFbR2 mutant biliary tract cancers ( 105 ) and in mouse models with constitutively active AKT/YAP pathway ( 106 , 107 ). Moreover, IL33 is overexpressed in human gallbladder cancer patients ( 108 ). However, in pancreatic cancer patients high IL33 expression and high number of tumor-infiltrating ILC2s correlated with better survival ( 41 ).…”
Section: Il33 and Mast Cells In Gastrointestinal Cancermentioning
confidence: 99%